Recovered after an extreme bottleneck and saved by ex situ management: Lessons from the Alagoas curassow (Pauxi mitu [Linnaeus, 1766]; Aves, Galliformes, Cracidae). Issue 1 (26th October 2020) - Francisco, Mercival R.; Costa, Mariellen C.; Azeredo, Roberto M. A.; Simpson, James G. P.; da Costa Dias, Thiago; Fonseca, Alberto; Pinto, Fernando J. M.; Silveira, Luís F.
Abstract: A pivotal debate on biodiversity conservation is whether the scarce budgets must be invested in critically endangered taxa or in those with higher chances to survive due to larger population sizes. Addressing the fate of extremely bottlenecked taxa is an ideal way to test this idea, but empirical cases are surprisingly limited. The reintroduction of the extinct‐in‐the‐wild Alagoas curassow ( Pauxi mitu ) by Brazilian scientists in September 2019 added to the two other known cases of survival to bottlenecks of only two or three individuals. We exploit the reasons why this species has survived, and we report how investments to rescue the Alagoas curassow resulted in the protection of many other taxa, suggesting that in the face of the dramatic number of extinctions expected for the Anthropocene, integration must prevail over a choice. Abstract : Alagoas curassow ( Pauxi mitu ) is an endemic species from the Brazilian Atlantic Forest. It is considered extinct‐in‐the‐wild since the late 1970s. After an intensive captive breeding program and genetic management, this species recovered from one of the most severe bottlenecks recorded for a vertebrate. Alagoas curassow was released into its natural habitat in 2019, being the first extinct‐in‐the‐wild species to be reintroduced in South America. Highlights: Alagoas curassow was the first extinct‐in‐the‐wild species to be reintroduced in South America. This species had one of the most severe bottlenecks ever recorded for a vertebrate, and all remaining individuals descend from three founders. After careful ex‐situ and genetic management, the captive population had heterozygosity recovering, allowing some individuals to be released in their natural habitat after 40 years from the last record.